2003
DOI: 10.1101/gr.911803
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Identifying Novel NF-κB-Regulated Immune Genes in the Human Genome

Abstract: Identifying novel NF-κB-regulated immune genes in the human genome is important to our understanding of immune mechanisms and immune diseases. We fit logistic regression models to the promoters of 62 known NF-κB-regulated immune genes, to find patterns of transcription factor binding in the promoters of genes with known immune function. Using these patterns, we scanned the promoters of additional genes to find matches to the patterns, selected those with NF-κB binding sites conserved in the mouse or fly, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 66 publications
4
26
0
Order By: Relevance
“…79 Therefore, we speculated that ITPKC plays a significant role in the immune system and is probably related to inflammation. The finding of the predicted nuclear factor-kB binding sequence in the promoter of ITPKC in an in silico study 83 is in accordance with our speculation.…”
Section: Identification Of Itpkc As a Susceptibility Gene For Kdsupporting
confidence: 90%
“…79 Therefore, we speculated that ITPKC plays a significant role in the immune system and is probably related to inflammation. The finding of the predicted nuclear factor-kB binding sequence in the promoter of ITPKC in an in silico study 83 is in accordance with our speculation.…”
Section: Identification Of Itpkc As a Susceptibility Gene For Kdsupporting
confidence: 90%
“…Therefore, we speculated that ITPKC might be related to inflammation. Previous in silico study (75), which has predicted NF-kB binding sequence in the promoter of ITPKC, supported the idea that ITPKC is a potent immune gene.…”
Section: Identification Of Inositol 145-trisphosphate 3-kinase C Assupporting
confidence: 48%
“…Previously, the number of binding motifs for a particular transcription factor has been successfully used to predict the response to a transcription factor and to predict gene expression patterns during the yeast cell cycle (55). A computational approach to identify NF-B-regulated genes has also shown that, among a group of immune genes, the region immediately upstream of the TSS (ϳ230 bp) contains the highest density of NF-B sites compared with regions further upstream or with the promoters of a random group of genes (56). Thus, a high density of higher affinity NF-B/Rel sites in proximal promoter regions may be an important criterion for the NF-B/Rel dependence of a gene.…”
Section: Discussionmentioning
confidence: 99%